„Toleranţă, coexistenţă, antagonism Percepţii ale diversităţii religioase în Transilvania, între Reformă şi Iluminism” (eds.) Joachim Bahlcke and Konrad Gündisch, Editura Mega, Cluj-Napoca, 2013, 393 p., ISBN 978-606-543-353-3 - OANCEA, Sever (Studia Universitatis Babeș-Bolyai Historia, 2015)
The book edited by Joachim Bahlcke and Konrad Gündisch represents the result of a conference held in Stuttgart in 2008. Several scholars from Germany, Hungary and Romania gathered together in order to speak about what the organizers of the conference called “Toleranz – Koexistenz – Antagonismus. Wahrnehmungen religiöser Vielfalt in Siebenbürgen zwischen Reformation und Aufklärung.“ As the title suggests, three centuries of the Transylvanian past are considered, the “specific” case concerning the topic of identities. Nonetheless, as the contents disclose, the situation of non-Christian groups is not addressed by this book. Therefore, in my view, it would have been more appropriate that at least the title should reflect this situation, by indicating that the book would be focusing on “Confessional diversity” (konfessionelle Vielfalt/ diversitate confesională), as for instance, the Jews (the community of Alba) do not represent the explicit theme of any of the articles.